EVALUATION OF ANTIBIOTIC USE IN PEDIATRIC TYPHOID FEVER IN THE INPATIENT INSTALLATION OF RSUD NORTH LOMBOK - Adriyan Suhada; Tuhfatul Ulya; Sri Rahmawati; Musparlin Halid (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2022)
The purpose of this study was to find out whether the use of antibiotics in typhoid fever patients at the inpatient installation of the North Lombok - Tanjung Hospital met the rationality requirements which included the right patient, the right dose, the right drug, and the right indication according to the medical service standards (SPM) of North Lombok Hospital - Tanjung in 2017. This research is a non-experimental study. The research was carried out at the North Lombok - Tanjung Hospital. The results showed that, according to inpatient medical record data available at the North Lombok - Tanjung Hospital in 2021, there were 14 cases of children diagnosed with typhoid fever. The results showed that the selection of the type of antibiotic used for the treatment of typhoid fever was chloramphenicol at 42.85%, then the antibiotics cefotaxime, cefixim, tiamfenicol and ceftriaxone each at 14.28%. After evaluating the use of antibiotics in pediatric patients with typhoid fever at Lombok Utara - Tanjung Hospital in 2021, the percentage value for using antibiotics with the right indication was 100%, the right drug was 85.71%, the right dose was 85.71%, and the right patient of 100%.